2003
DOI: 10.5713/ajas.2003.368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ammonia, Urea Plus Calcium Hydroxide and Animal Urine Treatments on Chemical Composition and In sacco Degradability of Rice Straw

Abstract: This experiment was conducted to examine the effects on the composition and rumen degradation in sacco of rice straw treated with animal urine (1 l of 2.9 g N/kg DM straw) and urea plus calcium hydroxide (2% urea plus 0.5% Ca(OH) 2 /kg DM straw) as a cheap and relatively safe alternative for ammonia (3% ammonia solution/kg DM straw). Mold occurred in urine treated straw, but other treatments were apparently mold-free. All treatments significantly (p<0.05) increased CP content in the straw compared with untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 13 publications
(16 reference statements)
4
9
1
Order By: Relevance
“…The increase of DM intake and DM, OM, CP, and NDF digestibility in urea-lime-treated rice straw treatments are consistent with the earlier findings of other researchers (Trach et al 2001;Fadel Elseed et al 2003;and Wanapat et al 2009). The increased DM intake was obtained when lowquality rice straw was treated with alkali agents which affected on cleavage of linkage between lignin and hemicellulose and cellulose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase of DM intake and DM, OM, CP, and NDF digestibility in urea-lime-treated rice straw treatments are consistent with the earlier findings of other researchers (Trach et al 2001;Fadel Elseed et al 2003;and Wanapat et al 2009). The increased DM intake was obtained when lowquality rice straw was treated with alkali agents which affected on cleavage of linkage between lignin and hemicellulose and cellulose.…”
Section: Discussionsupporting
confidence: 93%
“…However, in recent year, these approaches have so far been limited mainly due to economical reason and affecting on practical use by farmers. In an attempt to search for possible alternatives, rice straw treatments using urea plus lime have been studied by Fadel Elseed et al (2003) and Wanapat et al (2009) who reported that when amount of urea was reduced and combined with calcium hydroxide, the improvement in rumen fiber degradability and milk yield were obtained, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large quantities of poor quality roughages available for ammoniation in developing tropical countries, commercial application of this approach has so far been limited mainly to developed countries because of technical and economical constraints in the former. However, in an in situ study Fadel Elseed et al . (2003) suggested that, when amount of urea was reduced and combined with calcium hydroxide the improvement in rumen degradability was somewhat smaller than ammonia treatment but the technical and economical feasibility might give additional value to the urea‐calcium hydroxide treatment.…”
Section: Introductionmentioning
confidence: 95%
“…Although, urea-treated (5%) rice straw has been used as a roughage during the dry season but the cost was relatively high due to increasing price of urea (Wanapat, 1994;Preston, 1995). Fadel Elseed et al (2003) suggested that when amount of urea was reduced and combined with calcium hydroxide Ca (OH) 2 , it could improve rumen degradability. The concentrated alkaline agents can chemically break the ester bonds between lignin and hemicellulose and cellulose, and physically make structural fibers swollen.…”
Section: Introductionmentioning
confidence: 99%